Effectiveness of heartfulness meditation on cognitive and autonomic functions in women with premenstrual syndrome - Umadevi B; Nalina N; Sujaya B; Sai Sailesh Kumar Goothy (Asian Journal of Medical Sciences, 2023)
Background: Heartfulness meditation is heart-based meditation that helps to balance the mental status. The relaxation offered by meditation is so valuable as it not only improves quality but also improves the quantity of life. However, there is a requirement for the long-term practice of these meditations to receive their effects. The relaxation offered by meditation is very promising that it causes improvement in cognitive functions and sleep patterns. Aims and Objectives: The present study was undertaken to observe the effectiveness of heartfulness meditation on cognitive and autonomic functions in women with premenstrual syndrome (PMS). Materials and Methods: The present study was an experimental study. A total of forty females with PMS were part of the study. After recording the baseline values in the pre-menstrual period, the participants were trained in heartfulness meditation for weekdays by an expert. Later, they were asked to practice the heartfulness meditation daily for half an hour for 8 weeks at the meditation center of the college. After 8 weeks of practice of the heartfulness meditation, post-intervention values were recorded. Cognitive parameters were assessed using the spatial and verbal memory tests. Blood pressure and pulse rate were assessed using a diamond digital sphygmomanometer. Results: There was a significant improvement in spatial memory, and verbal memory scores followed by meditation. There was a significant decrease in systolic and diastolic blood pressure and pulse rate followed by the intervention. Conclusion: The study results in support earlier studies as there was a significant improvement in the cognitive scores and a decrease in the autonomic parameters in the participants followed by the practice of the heartfulness meditation. Further detailed studies are recommended to support the incorporation of heartfulness meditation into the routine day lifestyle.